Labor Markets, Stratiﬁ cation and Careers in Soviet Sociology - СоколовМихаил Михайлович (Journal of Economic Sociology, 2011)
The article is focused on the history of emergence and organization of academic markets of sociological profession in the late USSR. It starts with a description of niches occupied by the new professional specialization in soviet academic «ecologies» (Andrew Abbott) and conﬂ icts inherent to this division of labor. Major subspecializations and characteristics of their representatives are analyzed. The role of political patronage imposed by the philosophy-and-party bosses is discussed. Finally, the mechanics of academic statuses and professional contracts distribution is laid out.